Antifungal pharmacodynamics : Latin America’s perspective (2017)
ABSTRACT: The current increment of invasive fungal infections and the availability of new broad- spectrum antifungal agents has increased the use of these agents by non-expert practitioners, without an impact on mortality. To improve efficacy while minimizing prescription errors and to reduce the high monetary cost to the health systems, the principles of pharmacokinetics (PK) and pharmacodynamics (PD) are necessary. A systematic review of the PD of antifungals agents was performed aiming at the practicing physician without expertise in this field. The initial section of this review focuses on the general concepts of antimicrobial PD. In vitro studies, fungal susceptibility and antifungal serum concentrations are related with different doses and dosing schedules, determining the PD indices and the magnitude required to obtain a specific outcome. Herein the PD of the most used antifungal drug classes in Latin America (polyenes, azoles, and echinocandins) is discussed.